miR-155 harnesses Phf19 to potentiate cancer immunotherapy through epigenetic reprogramming of CD8+ T cell fate - Ji, Yun; Fioravanti, Jessica; Zhu, Wei; Wang, Hongjun; Wu, Tuoqi; Hui, Jinhui; Lacey, Neal E.; Gautam, Sanjivan; Le Gall, John B.; Yang, Xia; Hocker, James D.; Escobar, Thelma M.; et al. (Nature Communications, 2019)
T cell senescence and exhaustion are major barriers to successful cancer immunotherapy. Here we show that miR-155 increases CD8+ T cell antitumor function by restraining T cell senescence and functional exhaustion through epigenetic silencing of drivers of terminal differentiation. miR-155 enhances Polycomb repressor complex 2 (PRC2) activity indirectly by promoting the expression of the PRC2-associated factor Phf19 through downregulation of the Akt inhibitor, Ship1. Phf19 orchestrates a transcriptional program extensively shared with miR-155 to restrain T cell senescvbence and sustain CD8+ T cell antitumor responses. These effects rely on Phf19 histone-binding capacity, which is critical for the recruitment of PRC2 to the target chromatin. These findings establish the miR-155–Phf19–PRC2 as a pivotal axis regulating CD8+ T cell differentiation, thereby paving new ways for potentiating cancer immunotherapy through epigenetic reprogramming of CD8+ T cell fate.
CRIS-Team Scopus Importer:2023-03-23